Determinants of patient activation in a community sample of breast and prostate cancer survivors. Issue 1 (28th February 2017) - O'Malley, Denalee; Dewan, Asa A.; Ohman‐Strickland, Pamela A.; Gundersen, Daniel A.; Miller, Suzanne M.; Hudson, Shawna V.
Abstract: Background: Patient activation—the knowledge, skills, and confidence to manage one's health—is associated with improved self‐management behaviors for several chronic conditions. This study assesses rates of patient activation in breast and prostate cancer survivors and explores the characteristics associated with patient activation. Methods: A cross‐sectional study of survivors with localized (Stage I or II) breast and prostate cancers who were post‐treatment (between 1‐10+ years) were recruited from 4 community hospital sites in New Jersey. Survey data on patient characteristics (demographic and psychosocial) and clinical factors were assessed to explore the relationships with patient activation using the Patient Activation Measure–13. Results: Among 325 survivors (112 prostate; 213 breast), overall patient activation was high (M = 3.25). Activation was significantly lower among prostate survivors when compared with breast cancer survivors (M = 3.25 [SD, 0.38] vs M = 3.34 [SD, 0.37], P<.05). For prostate survivors, race (P < .05), marital status (P < .001), employment status (P < .01), household income (P < .05), and fear of recurrence (P < .01) were significantly associated with patient activation. For both groups, ease of access to oncology team and primary care physicians (PCPs) (all P values < .001) and perceptions of time spent with oncologists' team and PCPs (all P values < .01) were positive predictors of activation. Conclusions: In both breast and prostate survivors, access to providers (both PCPs and oncologists) and perception that adequate time spent with providers were associated with activation. Therefore, clinical interventions maybe a promising avenue to improve patient activation. Research is needed to develop and test tailored patient activation interventions to improve self‐management among cancer survivors.